Climate Services: An efficient adaptation strategy to impending climate change in Indian Agriculture - V, Manjunath K; Garai, Sanchita; MAITI, SANJIT (Indian Farming, 2022)
Climate change affects all three aspects of food security: availability, access and absorption. Climate change has about 4–9% impact on agriculture each year. As agriculture contributes 15% to India’s GDP, climate change presumably causes about 1.5% loss in GDP. Adaptation has become a national priority for many countries, where this supply of seamless climate services containing advisories for farm and livestock operation is disseminated well in advance of the impending weather, and is playing a pivotal role in the management of climate risks in agriculture. These services are critical to improving decision-making in climate-sensitive sectors like agriculture. Wise use of climate services can help to make better-informed policy, institutional and community decisions that reduce related risks and enhance opportunities, improve the efficient use of limited resources and increase crop and livestock production. Climate services have demonstrably led to improved agricultural and food security outcomes and benefits for stakeholders in the sector across the globe.